A nano interlayer spacing and rich defect 1T-MoS2 as cathode for superior performance aqueous zinc-ion batteries. Issue 13 (1st June 2021) - Cai, Chengyan; Tao, Zengren; Zhu, Yuanfei; Tan, Yuanming; Wang, Anding; Zhou, Haiyun; Yang, Yangyi
Abstract : A simple hydrothermal method is used to synthesize molybdenum disulfide with nano-level interlayer spacing, which effectively improves the zinc storage performance as a cathode electrode in aqueous zinc-ion batteries. Abstract : Aqueous Zn-ion batteries (ZIBs) are considered very promising alternatives to lithium-ion batteries. However, the low reversibility and slow diffusion of zinc ions in the positive electrode limit their commercial applications. Herein, we successfully prepared the metallic 1T phase of MoS2 (1T-MoS2 ) with a nano interlayer spacing of 1.025 nm through a simple one-step hydrothermal method, and used it as a cathode in ZIBs. By adjusting the hydrothermal temperature, the crystallinity and Zn 2+ storage capacity of MoS2 as a cathode for ZIBs are effectively improved. MoS2 had the most favorable structure when the hydrothermal temperature was 200 °C, such as larger layer spacing and more lattice distortion. When employed as a cathode, 200-MoS2 exhibited a considerable specific capacity of 125 mA h g −1 at the current density of 2 A g −1 and high capacity retention of 100% after 500 cycles. This strategy provides a new option for improving the performance of the layered structure as an aqueous zinc ion battery.